PENGEMBANGAN E-LKPD BERBASIS LIVEWORKSHEET PADA TEMA 1 SUBTEMA 1 PEMBELAJARAN 3 - Raden Rani Nurafriani; Yuli Mulyawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the development of Liveworksheet-based E-LKPD to be developed to Class V of SDN Cisarua 03 and to determine the feasibility of Liveworksheet-based E-LKPD for the learning process carried out in schools. The method used in this study was to use the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation), in this study, validation tests were carried out to experts. These experts are media experts, linguists and material experts to develop and perfect Liveworksheet-based E-LKPD to students, and distribute student questionnaire sheets to find out the feasibility of Liveworksheet-based E-LKPD on learning. The results of the validation test by media experts with a percentage of 82.85% with decent criteria, linguists with a percentage of 85% with decent criteria and material experts with a percentage of 98% with very decent criteria. And the results of the student response questionnaire showed results with a percentage of 90.21% with a very good category, so these results showed that E-LKPD was very feasible to be developed for students and was very worthy of being used as a learning tool in the learning process.